QUR’ĀNIC INTERPRETATION POLITICIZED: ASMA BARLAS’ TEXT REREADING - Adam, Ibrahim Ilyasu (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
This paper examines the role of Muslim feminist scholars in the reinterpretation of the Qur’ān within the discourse of Islamic feminism with particular reference to Asma Barlas, a controversial ’Qur’ān-only’ feminist. In pursuance of their identity struggle, Muslim feminists adopted new gender sensitive methodology of text rereading to prove their worth. This is particularly true for Barlas who concisely argues that traditional exegetes manipulated Quranic interpretation in their favour to oppress women and to establish their ’male-centric’ authority. In other words, classical methodology of tafsir is patriarchal, misogynistic and anti-woman. Hence, re-contextualization of the Qur’ān through adopting new gender orientated methodology of interpretation is not only desirable, but also necessary. For Barlas, this will ensure active participation of women in tafsir and create a link between Quranic hermeneutics and the project of gender equality. This paper critically analyses Barlas’s views within the Islamic paradigm and examines to what extent she did break with patriarchal tradition in tafsir. Furthermore, it concludes that Barlas’ rereading of text is nothing, but a biased attempt to politicise Quranic interpretation and to provide theological legitimacy to a secular orientated discourse, Islamic feminism.